Associations between ecological diversity and rodent plague circulation in Yunnan Province, China, 1983-2020: A data-informed modelling study. - Ruiyun Li; Chao Su; Zhe Lou; Zhizhong Song; Ennian Pu; Yuqiong Li; Zihou Gao (Public Library of Science (PLoS), 2023)
Background Following its resurgence in 1982, rodent plague has been linked to a wide range of circulation risks in Yunnan Province. The most serious public health concern associated with effective plague control is determining how various ecological variables influence the differential risk of transmission. Methods We investigated the population dynamics of the hosts and vectors using large-scale epidemiological surveillance data. In a seasonal eco-epidemiological model, we evaluated the impact of ecological conditions on the vectored flea index (VFI) to determine the rate of plague transmission. Results The findings revealed a changing species composition in natural foci over time. Additionally, shifting distributional ranges of species by elevation may be vital in modulating the VFI. The model estimates indicate that the dynamic VFI contributes to spatiotemporal variance in transmission. Conclusions The VFI could be a critical ecological indicator, allowing for real-time tracking and prompt intervention in the circulation of rodent plague. Understanding eco-epidemiological diversity can provide essential insights into effective responses to future plague resurgence.